Protein microarray – modern technique used in proteomics - Nowak, Karolina (European Journal of Clinical and Experimental Medicine, 2011)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Proteomics is a field of science that studies the structure, function, location of proteins, post-translational modifications and interactions with other proteins. Protein microarray tchnology has become a crucial tool for large-scale and high-throughput research in proteomics. It allows fast, easy and parallel detection of thousands proteins in a single experiment. It has been applied to analyse antibody-antigen, protein-protein, protein-nucleic acid, potein-lipid and proteinsmall molecule interactions, as well as enzyme-substrate interactions. In the past few years, protein microarray technology has shown its great potential in basic research, diagnostics and drug discovery. This article reviews current methods in the generation and applications of protein microarrays.